BK polyomavirus and cytomegalovirus – a closer link than expected?. Issue 9 (13th August 2019) - Pape, Lars
Abstract : Valganciclovir prophylaxis for CMV might increase the risk for BKPyV viremia, consequently leading to revision and personalization of antiviral prevention strategies. Reischig et al's article is onpage 2457 .